Complete Ectopia Cordis: A Case Report and Literature Review - Simon Pius; Halima Abubakar Ibrahim; Mustapha Bello; Mohammed Bashir Tahir (Case Reports in Pediatrics)
Ectopia cordis is a congenital heart exposure defined as complete or partial protrusion of heart through ventral defect in the thoracoabdominal wall alone or with other viscera in cases of pentalogy of Cantrell. This condition was first described by Haller et al. in 1706; since then many advances have been made. Diagnosis of ectopia cordis is done prenatally in well-equipped health facility by antenatal ultrasound scan so that early diagnosis and management plan can be initiated. The index case was delivered to uneducated rural family and admitted at 3 days of life and survived for seven days, even though most literatures state that majority died within four days even with surgery. So, in view of this, we presented this case report to deliberately draw the attention of paediatrician/obstetrician to the fact that even though this condition is rare, proactive search and diagnosis should be made and early treatment should be instituted, so that such a child may be salvaged.